Penyuluhan pendidikan lingkungan hidup kawasan ekonomi khusus mandalika Lombok Tengah - Muaini Muaini; Rosada Rosada; Ahmad Afandi; Putri Maya Masyitah; Dian Eka Mayasari; Ilmiawan Mubin; Syukuriadi Syukuriadi (Universitas Muhammadiyah Mataram, 2024)
AbstractEnvironmental education consulting to the community aims to help the community in the tourist area by educating the importance of protecting the surrounding environment. Each individual must have a sense of responsibility for the environment and a caring attitude to protect the environment. The purpose of this activity is to increase the community's knowledge and insight in clean and healthy environmental awareness education. The level of awareness and community participation in the field of environmental protection is quite high, but the level of awareness still needs to be increased so that it can continuously influence knowledge and behavior and encourage widespread activity or real action in an effort to keep the environment clean. The method used to achieve the goals and objectives that have been set is by conducting training and counseling activities that are expected to be useful for the community and tourism managers. The results of the consultation activities can provide insights into science, understanding how to maintain the surrounding environment in the tourist area and preserve the surrounding natural environment from the impact of tourism development. The community enthusiastically participated in the extension activities in Sade Rembitan Village, Pujut District, Central Lombok Regency. Keywords: environmental education; special economic zones. AbstrakPenyuluhan pendidikan lingkungan hidup kepada masyarakat bertujuan untuk membantu masyarakat dikawasan wisata dengan mengidukasi pentingnya menjaga lingkungan sekitar. Setiap individu harus memiliki rasa tanggung jawab terhadap lingkungan dan sikap peduli untuk menjaga lingkungan. Tujuan kegiatan ini adalah untuk meningkatkan pengetahuan dan wawasan masyarakat mengenai pendidikan penyadaran lingkungan bersih da sehat. Tingkat kependulian dan peran serta masyarakat dalam bidang pelestarian lingkungan sudah cukup tinggi, tetapi tingkat kependulian tersebut masih perlu ditingkatkan sehingga dapat mempengaruhi pengetahuan dan perilaku secara terus menerus serta mendorong aktivitas atau tindakan nayata secara meluas dalam usaha menjaga kebersihan lingkungan. Metode yang digunakan untuk mencapai tujuan dan targetyang telah ditetapkan adalah dengan cara melaksanakan pelatihan dan penyuluhan yang diharapkan berguna bagi masyarakat dan pengelola wisata. Hasil dari kegiatan penyuluhan dapat memberikan wawasan ilmu pengetahuan, pemahaman cara menjaga lingkungan sekitar yang berada di kawasan wisata dan menjaga lingkungan alam sekitar dari dampak perkembangan pariwisata. Masyarakat antusias mengikuti kegiatan penyuluhan di Sade Desa Rembitan Kecamatan Pujut Kabupaten Lombok Tengah. Kata kunci: pendidikan lingkungan hidup; kawasan ekonomi khusus.